The Audience’s Response to Gender Relation Campaign of Ketchup Brand on Youtube - Muchammad Nasucha; Rizky Kertanegara (Universitas Multimedia Nusantara, 2020)
Currently, the rapid usage of the Internet as a tool or medium of communication and information, including media campaign to society, is popular to spread the idea(s), thought, even ideology. YouTube, as one of the popular video-sharing social media, is vivacious and potential to get the audience’s attention and responses accordingly to the design(s) like ABC as one of the brands of complementary food (sauce/ketchup) has done. This research tries to find the audience’s responses to gendered-relations campaign through the new media, particularly through social media (YouTube). Based on reader-response theory and using [dominantly] qualitative text online analysis, this research attempts to find the variety of the audience’s response to the Campaign. Finally, this research finds that basically, the responses are implicit and explicit. The explicit means that the icon like and unlike identifies the audience’s positive and negative responses. The implicit response appears in the comment section, both verbal and nonverbal (such as emoticon). We can catch many comments about gender relations. Even between wife-husband (spousal relationship), the dichotomy still exists and shows a negative-positive pole. The diverse responses/comments presented by the audiences seem to be influenced by several factors, such as values of the culture, education, family, environment, society, and religion. It seems that the campaign as a digital marketing strategy has affected the audiences to involve in spreading the idea, called as the word-of-mouth effect. Keywords: audience response, Campaign, gender relation, social media, digital marketing